Strategic planning and governance in the recovery of touristic destinations affected by unnatural disasters. State of the question - Manuel Rivera Mateos; Ángel Guillermo Félix Mendoza (Investigaciones Geográficas)
This paper systematically reviews strategic planning models implemented in tourist destinations affected by natural disasters. For this, case studies from various regions are analysed to identify key research topics, the most common strategies, connection points, and the most innovative methodologies, as well as systematising the most successful experiences. A synthesis of characteristics found shows that, although certain regularities appear, researchers have not reached a consensus regarding the selection of factors and measures to be included in the strategic recovery plans of destinations after a crisis, nor in the methodology for its instrumentation. No model can be considered complete because each contains strengths and opportunities, but also limitations and weaknesses. After a discussion of results and validity, guidelines are proposed for cases of affected destinations in aspects such as recovery of image, marketing, cooperation between actors, governance system, or the revaluation and requalification of the heritage offer and tourist services.